Alternative Splicing as a Regulator of Early Plant Development - Szakonyi, Dóra; Duque, Paula (Frontiers in Plant Science, 2018)
Most plant genes are interrupted by introns and the corresponding transcripts need to undergo pre-mRNA splicing to remove these intervening sequences. Alternative splicing (AS) is an important posttranscriptional process that creates multiple mRNA variants from a single pre-mRNA molecule, thereby enhancing the coding and regulatory potential of genomes. In plants, this mechanism has been implicated in the response to environmental cues, including abiotic and biotic stresses, in the regulation of key developmental processes such as flowering, and in circadian timekeeping. The early plant development steps – from embryo formation and seed germination to skoto- and photomorphogenesis – are critical to both execute the correct body plan and initiate a new reproductive cycle. We review here the available evidence for the involvement of AS and various splicing factors in the initial stages of plant development, while highlighting recent findings as well as potential future challenges.